Effects of nano urea on Indian mustard (Brassica juncea) productivity and nutrient uptake in calcareous soils - MEENA, MUKESH KUMAR; SINGH, HAR VIR; JAT, RAM SWAROOP; DOTANIYA, MOHAN LAL; MEENA, MURALI DHAR; CHOUDHARY, RAM LAL; MEENA, VASUDEV; MEENA, PRABHU DAYAL; RAI, PROMOD KUMAR (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during winter (rabi) seasons of 2021–22 and 2022–23 at ICAR-Directorate of Rapeseed Mustard Research, Bharatpur, Rajasthan to assess the effect of nano urea (NU) spray in conjunction with different rates of soil applied fertilizer (conventional urea) N on growth, yield, nutrient content and uptake of Indian mustard [Brassica juncea (L.) Czern. and Coss.] in a calcareous soil of arid and semi-arid region. The experiment was conducted in a randomized complete block design (RCBD) and replicated thrice The treatment combinations consisted of basal applications of fertilizers and foliar spray (FS) of nano urea (NU) either once 30 days after sowing (DAS) or twice 30 and 50–55 DAS. The field experiment comprised of 9 treatments, viz. Control; Recommended dose of fertilizer (RDF); RDN25 + NU-1FS; RDN25 + NU-2FS; RDN50 + NU-1FS; RDN50 + NU-2FS; RDN100 + NU-1FS; RDN75 + NU-1FS; and RDN75 + NU-2FS. Results revealed that treatment RDN100 + NU-1FS (single sprays of nano urea together with the 100% prescribed dose of N) produced the maximum values of 24.30 and 66.62 q/ha yield of seed and stover, respectively. However, RDN75 + NU-2FS produced statistically comparable yield to the treatment RDN100 + NU-1FS. By applying nano urea, the recommended N dose can be reduced up to 25% without compromising yield. One FS of NU with RDN100 registered highest plant height, main shoot length, main shoot siliquae number, total siliquae number/plant and the number of secondary branches of the plant, and proved superior over other treatments. Further, results exhibited that RDN100 + NU-1FS increased N, P, and K uptake values to 66.74, 10.42, and 17.85 kg/ha in seed and 44.23, 9.48, and 78.98 kg/ha in stover. Overall, it has been determined that the most efficient way to increase the yield, concentration, and uptake of N, P, and K in Indian mustard is to apply nano urea foliar at 30 and 60 DAS in conjunction with RDF.